Digital Leadership in IT Organizations: A Narrative Review of Strategies and Challenges in the Era of Disruption - Prasetya, Yuli (Indonesian Scientific Publication, 2025)
This narrative review investigates the evolving role of digital leadership in facilitating transformation within IT-driven organizations. The study aims to explore how digital leadership shapes strategic and operational changes amid accelerating technological advancements. A structured literature search was conducted across Scopus, Web of Science, and Google Scholar using key terms including